2019
DOI: 10.1038/s41598-018-36471-4
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytoma progression scoring system based on the WHO 2016 criteria

Abstract: Diffuse astrocytoma (including glioblastoma) is morbid with a worse prognosis than other types of glioma. Therefore, we sought to build a progression-associated score to improve malignancy and prognostic predictions for astrocytoma. The astrocytoma progression (AP) score was constructed through bioinformatics analyses of the training cohort (TCGA RNA-seq) and included 18 genes representing distinct aspects of regulation during astrocytoma progression. This classifier could successfully discriminate patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Like IDH-mutant lower-grade gliomas, more complex multi-gene and multi-CNV prognostic schemes have also been devised for the IDH-mutant GBM category [65,68,69], and large scale studies have shown that there are multiple genetic and epigenetic phenotypes that can result in longer survival in GBM cohorts [113]. MGMT Promoter methylation predicts improved response to temozolomide [122,123] CCND2 Amplification is correlated with better clinical outcome [115] Total copy number variation (CNV)…”
Section: Idh-mutant Glioblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…Like IDH-mutant lower-grade gliomas, more complex multi-gene and multi-CNV prognostic schemes have also been devised for the IDH-mutant GBM category [65,68,69], and large scale studies have shown that there are multiple genetic and epigenetic phenotypes that can result in longer survival in GBM cohorts [113]. MGMT Promoter methylation predicts improved response to temozolomide [122,123] CCND2 Amplification is correlated with better clinical outcome [115] Total copy number variation (CNV)…”
Section: Idh-mutant Glioblastomamentioning
confidence: 99%
“…Others have reported a shortened time to malignant progression with increased nuclear immunohistochemical expression of cMYC protein [ 60 ] and worse prognosis with increased nestin immunohistochemistry [ 61 ]. Multiple other specific genetic and immunohistochemical factors have also been considered, including c-MET, EMP3 , GSX2 , EMILIN3 , PPIC , and CHI3L1 [ 62 , 63 , 64 ], and multiple algorithms and multi-gene/multi-CNV panels have been suggested with varying technical complexity, practicality, and prognostic power [ 44 , 49 , 65 , 66 , 67 , 68 , 69 ]. These multi-gene models suggest that in many cases, there are alterations in multiple pathways acting in concert to determine the biologic behavior of the tumor, however, for practical purposes, these panels will likely need to be pared down to key alterations that can be identified soon after the initial histologic diagnosis.…”
Section: Idh-mutant Lower-grade Astrocytomamentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, the latter group is the most aggressive type and to date, non-curable [48,49]. Astrocytoma derive from star-shaped glia cells that are called astrocytes [50]. Glioma cells firstly experience disrupted pathways of cell cycle control, including mutations in p16, CDK-4, cyclin D1 and RB1 [51].…”
Section: Signaling Backgroundmentioning
confidence: 99%
“…Conversely, the second group includes those gliomas that are more difficult to treat because of their heterogeneity and invasive growth. These include diffuse astrocytoma (grade II), anaplastic astrocytoma (AA, grade III), and glioblastoma (GBM, grade IV) [1,2]. Depending on the presence or absence of isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) gene mutations, this last group of tumors can be subclassified into IDH-mutant and IDH-wildtype categories, of which the first type is associated with better prognosis [3,4].…”
Section: Introductionmentioning
confidence: 99%